EVALUATION OF ELECTRONIC GOVERNMENT SECURITY ISSUES APPLIED TO COMPUTER CENTER OF BAGHDAD UNIVERSITY (CASE STUDY) (Journal of Engineering, 2012)
Information security contributes directly to increase the level of trust between the government’s departments by providing an assurance of confidentiality, integrity, and availability of sensitive governmental information. Many threats that are caused mainly by malicious acts can shutdown the egovernment services. Therefore the governments are urged to implement security in e-government projects. Some modifications were proposed to the security assessment multi-layer model (Sabri model) to be more comprehensive model and more convenient for the Iraqi government. The proposed model can be used as a tool to assess the level of security readiness of government departments, a checklist for the required security measures and as a common security reference in the government organizations of Iraq. In order to make this model more practical, applicable and to represent the security readiness with a numerical value, evaluation modeling has been done for this model by using fuzzy logic tool of MATLAB R2010a program. Since the risk assessment is considered as a major part in the information security management system, an effective and practical method to assess security risk is proposed by combining FEMRA (fuzzy expert model risk assessment) and Wavelet Neural Network (WNN). The fuzzy system is used to generate the training data  set in order to make the required training for WNN. The proposed method is applied when a risk assessment case study is made at the computer center of Baghdad University. It is found from the numerical results that the risk levels obtained by WNN are (with maximum of 58.23) too close to these calculated from FEMRA (with maximum of 60), with an average error of 5.51%. According to these results, the proposed method is effective and reasonable and can provide the support toward establishing the e-government.